Effect of compost and biochar on soil fertility and cabbage yield - Abbey, Charlotte (University of Cape Coast, 2019)
Soil fertility decline remains the major biophysical constraint to low crop productivity on farmlands. Even though inorganic fertilizers play significant role in increasing crop production, they are not a sustainable solution in maintaining high crop yields as it gradually deteriorates soil physico-chemical properties which subsequently reduce crop yield. Both pot and field experiments were conducted to determine the effect of combined application of compost and biochar on soil pH, total nitrogen, available phosphorus, nutrient use and efficiency, total organic carbon, bulk density, field capacity, hydraulic conductivity as well as the yield of cabbage (test crop). A completely randomised design and randomised complete block design were used for pot and field experiments respectively with 3 cabbage varieties for the pot and 2 cabbage varieties for the field. Total microbial count in log/cfu was determined using the total plate count. Five treatments were evaluated, sole biochar (B), sole compost (C), compost + biochar (CB), NPK fertilizer (NPK) and control (no application). There was no significant difference among the treatments in all the soil parameters measured for pot experiment except the pH for NPK which was lower (5.83) compared to B (6.58), C (6.47) and CB (6.51). In the field experiment, B and CB increased total organic carbon (1.21% and 1.54% respectively). The C and CB increased the crop yield, soil total N and soil available P concentrations. Application B also increased soil microbial population. A combination of compost and biochar can therefore be used as a soil amendment to increase yield and improve soil physico-chemical properties under field conditions.
xv,98;,ill
Keywords: Fertility; Cabbage Yield; Biochar; Compost